Komitmen Pimpinan Pondok Pesantren Sa’adatuddaren Jambi dalam Pengelolaan Program Pendidikan Kesetaraan Paket B - Sulbani Sulbani; Mukhtar Mukhtar; Hidayat Hidayat (INNOVATIO: Journal for Religious Innovation Studies, 2018)
The commitment of a high school principal can lead to the success of the work of educational organizations by improving the quality of education. The leadership commitment of the Sa’adatuddaren Islamic Boarding School in the management of the Package B or Equality Education Program in Pelayangan District, Jambi City was examined using qualitative methods. The purpose of this study was to review the commitment of the leaders of the Sa’adatuddaren Islamic Boarding School in the management of the Package B Equality Education Program. Data collected through observation, interview and documentation techniques. Determination of research subjects using purposive sampling technique. Data analysis techniques were carried out by reducing data, presenting data and drawing conclusions as well as verifying the reliability of the results obtained by the technique of extension of participation, accuracy of observations, data triangulation and advisory consultation. Based on the data obtained, the commitment of the Sa’adatuddaren leadership in the management of the Package B Equality Education Program at the Islamic Boarding School still low action. There is no priority scale for the improvement of the Package B Equality Education Program annually